ANALISIS TAHAPAN PERKEMBANGAN RIVERFRONT TOURISM DI INDONESIA - Fithria Khairina Damanik; Bhernadetta Pravita Wahyuningtyas; Heru Purboyo Hidayat Putro (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2025)
Indonesia has approximately 7,000 rivers, most of which have experienced significant degradation in quality and are in alarming conditions. Many cities in Indonesia have historically developed along riverbanks, making the decline of these waterways particularly concerning. The deterioration of river quality and riverbank areas is attributed to various factors, including pollution, deforestation, and the uncontrolled disposal of industrial and domestic waste. These issues not only threaten the health of river ecosystems but also jeopardize the sustainability of communities that depend on these natural resources and contribute to various urban challenges. Communities residing in riverbank settlements are among the most affected by these environmental issues. Therefore, they require clear and accurate information regarding the dangers of pollution and the importance of maintaining river cleanliness. This research is conducted in qualitative approach with descriptive analysis technique. This study examines the development of riverbank areas in Indonesian cities by referring to the stages of waterfront development proposed by Wrenn (1983). Additionally, it explores the concept of riverfront tourism as a form of urban regeneration and urban tourism development. The regeneration of riverbank areas for tourism purposes is expected to raise awareness among stakeholders regarding the social and environmental significance of these areas. If properly developed, riverfront tourism can contribute to the enhancement of destination quality, fostering sustainable and competitive tourism development.